Hexagonal TiO2/SiO2 Porous Microplates for Methylene Blue Photodegradation - Ulfa, Maria; Anggreani, Cindy Nur; Mulyani, Bakti; Sholeha, Novia Amalia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Hexagonal TiO2/SiO2 Porous Microplates have been successfully synthesized by incorporation of Ti precursors into SiO2 synthesized from Si precursors in a gelatin-CTAB mixture via the hydrothermal method. The prepared samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), EDX, nitrogen adsorption-desorption and Fourier transform infrared spectroscopy (FTIR). The sample has a surface area of 735 m2/g, pore volume of 0.67 cc/g, and pore diameter of 3.2 nm, according to the results of the characterization of hexagonal TiO2/SiO2 porous microplates. The transformation of SiO2 microspheres into hexagonal TiO2/SiO2 porous microplates is revealed by a microparticle size increase of 84% and the transition of Si−O bonds into Ti−O and Si−O as measured by FTIR. The photocatalytic activity of hexagonal TiO2/SiO2 porous microplates resulted in 81.15% photodegradation of methylene blue under UV light irradiation within 60 min, which was 21 % better than SiO2. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).